Fluorescent identification of axons, dendrites and soma of neuronal retinal ganglion cells with a genetic marker as a tool for facilitating the study of neurodegeneration - Puttipong Sripinun; Wennan Lu; Sergei Nikonov; Suhani Patel; Sarah Hennessy; Tianyuan Yao; Qi N. Cui; Brent A. Bell; Claire H. Mitchell (FASEB BioAdvances)
Abstract This study characterizes a fluorescent Slc17a6‐tdTomato neuronal reporter mouse line with strong labeling of axons throughout the optic nerve, of retinal ganglion cell (RGC) soma in the ganglion cell layer (GCL), and of RGC dendrites in the inner plexiform layer (IPL). The model facilitated assessment of RGC loss in models of degeneration and of RGC detection in mixed neural/glial cultures. The tdTomato signal showed strong overlap with >98% cells immunolabeled with RGC markers RBPMS or BRN3A, consistent with the ubiquitous presence of the vesicular glutamate transporter 2 (VGUT2, SLC17A6) in all RGC subtypes. There was no cross‐labeling of ChAT‐positive displaced amacrine cells in the GCL, although some signal emanated from the outer plexiform layer, consistent with horizontal cells. The fluorescence allowed rapid screening of RGC loss following optic nerve crush and intraocular pressure (IOP) elevation. The bright fluorescence also enabled non‐invasive monitoring of extensive neurite networks and neuron/astrocyte interactions in culture. Robust Ca2+ responses to P2X7R agonist BzATP were detected from fluorescent RGCs using Ca2+‐indicator Fura‐2. Fluorescence from axons and soma was detected in vivo with a confocal scanning laser ophthalmoscope (cSLO); automatic RGC soma counts enhanced through machine learning approached the numbers found in retinal wholemounts. Controls indicated no impact of Slc17a6‐tdTomato expression on light‐dependent neuronal function as measured with a microelectrode array (MEA), or on retinal structure as measured with optical coherence tomography (OCT). In summary, the bright fluorescence in axons, dendrites and soma of ~all RGCs in the Slc17a6‐tdTomato reporter mouse may facilitate the study of RGCs.